2015
DOI: 10.1186/s12885-015-1250-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of attitude and recommendation of oncologists toward exercise in South Korea: a cross sectional survey study

Abstract: BackgroundThe purpose of the present study was to examine 1) characteristics and attitudes of oncologists toward exercise and toward recommending exercise to their patients, 2) association among oncologists’ own physical activity levels, exercise recommendations, and their attitudes toward recommending exercise.MethodsA total of 167 oncologists participated in this survey study (41 surgeons, 78 medical oncologists, 25 radiation oncologists, and 21 others). Most oncologists included in the study treat more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 33 publications
9
58
2
1
Order By: Relevance
“…Multiple studies suggest that patients with cancer prefer to receive exercise recommendations from their oncologist, but data also indicate that barriers are in place that prevent routine physician-initiated discussion about exercise as part of a treatment plan. [11][12][13][14] In our study group, patients with and without metastatic disease consistently reported no recollection of physician-initiated conversations about exercise during their treatment. Jones and Courneya 15 found that most (≈82%) cancer survivors prefer that their oncologist initiate exercise discussions; still less than a third (28%) of survivors reported having had these discussions initiated by their oncologist.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Multiple studies suggest that patients with cancer prefer to receive exercise recommendations from their oncologist, but data also indicate that barriers are in place that prevent routine physician-initiated discussion about exercise as part of a treatment plan. [11][12][13][14] In our study group, patients with and without metastatic disease consistently reported no recollection of physician-initiated conversations about exercise during their treatment. Jones and Courneya 15 found that most (≈82%) cancer survivors prefer that their oncologist initiate exercise discussions; still less than a third (28%) of survivors reported having had these discussions initiated by their oncologist.…”
Section: Discussionmentioning
confidence: 64%
“…These results parallel those of previous studies reporting that 73% and 62% of oncologists agree that exercise is beneficial. 13,14 Yet only 2 providers in our group documented exercise recommendation in the electronic medical record >50% of the time; for the remainder, this rate was ≤25%. Our results are consistent with those of the Canadian provider group reporting a 28% recommendation rate.…”
Section: Discussionmentioning
confidence: 89%
“…As the cross‐sectional nature of our study does not allow any causal conclusions, future studies should assess actual physical activity recommendations in a longitudinal design. Lastly, as the response rate was relatively low (though typical for surveys of this nature) and internal consistencies were in questionable range for some TPB variables, generalizability of our findings might be limited.…”
Section: Discussionmentioning
confidence: 86%
“…Most recent studies focused on the new activity-paradigm and did not include the "old" rest-paradigm. 19,35,36 However, many HCP report insecurities about what to recommend to their cancer patients and concerns about physical overload and psychological stress. 23 Our research shows that although the rest-paradigm is outdated in research, it still seems to be relevant in oncological practice.…”
Section: Figure 1 Mean Comparison (T Tests)mentioning
confidence: 99%
“…During the treatment, patients with cancer encounter different health specialists who are potential promoters of PA, such as specialised physicians for certain cancer entities, general practitioners and oncology nurses. However, studies suggest that a considerable number of patients with cancer (30%–70%) do not receive a PA promotion by their physicians (Fisher et al., ; Karvinen, DuBose, Carney, & Allison, ; Park et al., ; Spellman, Craike, & Livingston, ; Williams, Beeken, Fisher, & Wardle, ). Few studies among oncology nurses indicate that they promote PA to patients with cancer more often than physicians (Karvinen, McGourty, Parent, & Walker, ; Kenison, Silverman, Sustin, & Thompson, ).…”
Section: Introductionmentioning
confidence: 99%